Implementation of the Concept of Teacher Service Excellence in Surah Al-Muddatstsir Verses 1-7 to Improve the Quality of Student Learning - Almuhajir, Almuhajir (JURNAL ISLAM NUSANTARA, 2023)
This research aims to analyze the implementation of the concept of teacher service excellence from the perspective of Surah al-Muddatstsir verses 1-7 to improve the quality of student learning. The researcher used a qualitative research method through a literature review with a bir-ra'yi (diroyah) interpretation approach, which included ar-Ra'yu al-Mahmudah. The data sources consist of primary data, namely the Al-Qur'an Surah al-Muddatstsir verses 1-7, and secondary data, several tafsir books, books, articles, or other relevant scientific works to this research. The data collection techniques used are documentation and content analysis. The results of the research show that the implementation of the teacher service excellence concept contained in Surah al-Muddatstsir verses 1-7 contains several aspects, including building personnel relationships, motivation and responsibility, vertical communication, appearance and cleanliness, self-purification and example, sincerity, and patience. The concept of teacher service excellence through the interpretation approach of Surah al-Muddatstsir verses 1-7 has a worldly and spiritual function. In general, it is very relevant to modern teacher service excellence. The concept of teacher service excellence through the interpretation approach of Surah al-Muddatstsir verses 1-7 is implemented into three dimensions, namely the dimensions of aqidah, akhlaq, and muamalah